Media Literacy and Its Implications for The Understanding of Truth and Reality: A Philosophical Exploration - Udoudom, Uduak; George, Kufre; Igiri, Anthony; Aruku, Kalita Joseph (Future Science / FSH-PH Publications, 2023)
In an era characterized by an overwhelming abundance of information and media channels, the concept of truth and reality has become increasingly complex. Media literacy, the ability to critically analyse, evaluate, and understand media messages, plays a crucial role in navigating this complexity. This paper explores the philosophical dimensions of media literacy and its implications for the understanding of truth and reality. Drawing on interdisciplinary perspectives from philosophy, communication studies, and cognitive science, this study investigates the intricate relationship between media literacy and the construction of truth and reality. By delving into various philosophical frameworks, including epistemology, ontology, and phenomenology, the research examined how individuals' media literacy skills shape their perceptions and interpretations of truth and reality. Additionally, the study examines how media literacy influences individuals' ontological understanding of reality. It explores how media messages shape and mediate individuals' perception of the world, examining the interplay between subjective experiences, social constructs, and media representations. Furthermore, the study investigated the potential for media literacy to foster a more nuanced understanding of reality, encouraging individuals to engage in critical reflexivity and challenge their preconceived notions. The findings of this study showed that media literacy plays a pivotal role in enhancing critical thinking skills and mitigating truth distortion in a post-truth society.